KEAUSAN BANTALAN BOLA YANG DI IMPLANTASI ION TiN DENGAN PELUMASAN GREASE - S. Sinarep (Universitas Mataram, 2011)
It has been conducted on the effect of ion implantation of TiN to wear ball bearings with grease lubrication. Ball bearing is one of the supporting components contained in the machine and the parts of a rotating element as found in automotive components. During the operation, this component causes the surface wear and vibration caused by continuous movement during loading. Ion implanted TiN ball bearing at the time of 90 minutes, the energy of 100 keV and current 10 μA are ring inside the outer ring, and ball as the wear test samples. Tests carried out with 3 variations of wear load and 3100 rpm shaft rotation. Grease is used to mark the torch. Then 3.9 grams of grease in then applied to the outer ring, inner ring and the ball. The test results showed that the wear volume increased with increasing the load on ball bearing non-implantation with grease lubrication, while the ion implanted TiN almost no increase. Wear resistance increased in metal ion implanted TiN. It is characterized by decreasing in wear rate when compared with non-metal implants. And traces of scratches experienced a very significant reduction in metal ion implanted TiN.